2014
DOI: 10.1002/stem.1767
|View full text |Cite
|
Sign up to set email alerts
|

Notch1 Stimulation Induces a Vascularization Switch With Pericyte-Like Cell Differentiation of Glioblastoma Stem Cells

Abstract: Glioblastoma multiforms (GBMs) are highly vascularized brain tumors containing a subpopulation of multipotent cancer stem cells. These cells closely interact with endothelial cells in neurovascular niches. In this study, we have uncovered a close link between the Notch1 pathway and the tumoral vascularization process of GBM stem cells. We observed that although the Notch1 receptor was activated, the typical target proteins (HES5, HEY1, and HEY2) were not or barely expressed in two explored GBM stem cell cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
92
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(103 citation statements)
references
References 62 publications
8
92
0
Order By: Relevance
“…A number of studies identified the genes and genetic pathways involved in the sustenance of GSCs, such as BMI1 and Notch (Baxter et al 2014;Guichet et al 2015;Schonberg et al 2014). However, as an important protein that participates in the synthesis of purines and pyrimidines, few studies have focused on the role of PRPS1 in tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies identified the genes and genetic pathways involved in the sustenance of GSCs, such as BMI1 and Notch (Baxter et al 2014;Guichet et al 2015;Schonberg et al 2014). However, as an important protein that participates in the synthesis of purines and pyrimidines, few studies have focused on the role of PRPS1 in tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…It remains unclear, however, whether MB cells have the potential to differentiate into pericytes, as shown for some other types of brain neoplastic cells that can generate pericytes to control blood vessel function during tumor growth 92,93 .…”
Section: Pericyte-endothelial Signal Transductionmentioning
confidence: 99%
“…More recent studies revealed that self-renewing tumorigenic glioma stem cells (GSCs) give rise to pericytes to support vessel formation and tumor growth 92,93 . GSCs are recruited to endothelial cells by the stromal-derived factor-1 (SDF-1), an alpha-chemokine that binds to G-protein-coupled CXCR4, and are induced to become pericytes predominantly by TGF-β 93 .…”
Section: Pericyte-endothelial Signal Transductionmentioning
confidence: 99%
“…The gene expression profiles of GSE44561 (Guichet et al, 2015), GSE48079 (Garner et al, 2013) and GSE22772 (Huber et al, 2013) were downloaded from National Center of Biotechnology Information (NCBI) Gene Expression Omnibus (GEO) database (Barrett et al, 2005) (http://www.ncbi.nlm.gov/geo/). A total number of eight samples for GSE44561 with activated Notch signaling pathway by a forced expression of the Notch intracellular domain were available, including four embryonic human neural stem cells samples and four GBM samples, and the platform was GPL11532.…”
Section: Microarray Datamentioning
confidence: 99%